A STUDY ON CONSUMER BRAND PREFERENCE OF AIR CONDITIONER IN POLLACHI TALUK (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The current market situation in India is extremely competitive in all  product segments. To survive in the market, it takes a lot of insight to understand consumers and offer the right product at the right price, in the right place, at the right time. To determine the factors influencing the consumers brand preference towards Air Conditioner . The data required for the study has been collected from 100 consumer in Pollachi Taluk using questionnaire method and collected data was analysed using simple percentage and chi-square test. This research identifies possible strategies to attract  consumers and make advance sales in the region. It is also suggested that companies focus their product availability more within reach of consumers. Tastes and preferences change frequently, so constant attention must be given to improving products to meet customer needs.